Investigation of Carmine Dye Removal by Green Chitin Nanowhiskers Adsorbent - Seyyed Salar Meshkat; Mojtaba Nasiri Nezhad; Mohammad Reza Bazmi (Emerging Science Journal, 2019)
A green adsorbent was evaluated to remove the carmine dye. Chitin nanowhiskers were synthesized via acid hydrolyzed method. The diameter of the synthesized chitin whiskers was about 20 nm and had 200 to 400 nm length. The morphology and chemical structure of the synthesized adsorbent were investigated by Field Emission Scanning Electron Microscopy (FESEM), Transmission Electron Microscopy (TEM), Fourier Transform Infrared (FT-IR), X- Ray Diffraction (XRD). The adsorption process parameters of the carmine dye removal were optimized as follow: adsorption time (3 h), initial carmine dye solution concentration (100 ppm), mass loaded of the chitin whiskers suspension 1% weight of chitin nanowhiskers, as an adsorbent (1.4 g). The removal efficiency of the carmine dye adsorption was about 85% which is modified 15% better than the previous researches. The results indicated that carmine dye molecules were absorbed by hydrogen bonding mechanism due to the N-H bond in the chitin nanowhiskers structure.